PTF 10fqs: A LUMINOUS RED NOVA IN THE SPIRAL GALAXY MESSIER 99 - Kasliwal, M; Kulkarni, SR; Arcavi, I; Quimby, R; Ofek, E; Nugent, P; Jacobsen, J; Gal-Yam, A; Green, Y; Yaron, O; Fox, D; Howell, J; et al. (2011)
The Palomar Transient Factory (PTF) is systematically charting the optical transient and variable sky. A primary science driver of PTF is building a complete inventory of transients in the local universe (distance less than 200 Mpc). Here, we report the discovery of PTF10fqs, a transient in the luminosity "gap" between novae and supernovae. Located on a spiral arm of Messier 99, PTF10fqs has a peak luminosity of Mr = -12.3, red color (g - r = 1.0), and is slowly evolving (decayed by 1mag in 68days). It has a spectrum dominated by intermediate-width Hα (930kms-1) and narrow calcium emission lines. The explosion signature (the light curve and spectra) is overall similar to that of M85OT2006-1, SN2008S, and NGC300OT. The origin of these events is shrouded in mystery and controversy (and in some cases, in dust). PTF10fqs shows some evidence of a broad feature (around 8600) that may suggest very large velocities (10,000kms-1) in this explosion. Ongoing surveys can be expected to find a few such events per year. Sensitive spectroscopy, infrared monitoring, and statistics (e.g., disk versus bulge) will eventually make it possible for astronomers to unravel the nature of these mysterious explosions. © 2011. The American Astronomical Society. All rights reserved.